CORRELATION BETWEEN STUDENTS WRITING ABILITY AND LEARNING MOTIVATION IN GOOGLE TRANSLATE WRITING CLASS - Arfiana Arfiana; Sabarun Sabarun; Hesty Widiastuty (IKIP Siliwangi, 2022)
This study was from the real phenomenon which showed that students were using google translate as media to improve their writing ability and learning motivation. The main problem was students’ lack of vocabulary and they wanted fast and instant translation. As a result, they preferred using google translate than doing their writing ability. The purpose of this research is to measure the correlation between students’ writing ability and learning motivation in google translate writing class of 2nd semester English education study program at IAIN Palangka Raya. This research was a correlational study using quantitative research method. Learning Motivation Questionnaire and Descriptive Text Writing Test were distributed to take the data from 58 student from 2nd semester in academic year 2020/2021 who took paragraph writing class. The sample was obtained through the use of the cluster random sampling technique. The result finding showed the calculation students’ writing ability and learning motivation was rvalue = 0.617 ≥ rtable = 0.258 and tvalue = 5.867118 ≥ ttable = 1.67252), it meant that Ha accepted and Ho rejected. In this case students’ writing ability had high relationship or gave influence to learning motivation in google translate class. Keywords: Correlation, Writing Ability, Learning Motivation, Google Translate